Optimalisasi Kinerja Gudang di PT. AB: Integrasi Strategis Analytical Hierarchy Process dan Balanced Scorecard - Rosyidah, Masayu; Malfitrah, M Fadli; Patradhiani, Rurry; Oktarini, Devie (Universitas Muhammadiyah Palembang, 2024)
This research aims to optimize the warehouse performance of PT. AB through the integration of the Analytical Hierarchy Process (AHP) and Balanced Scorecard (BSC) methodology. Facing challenges in warehouse operations, such as equipment reliability and labor efficiency, this study applies AHP to identify and prioritize critical factors that influence warehouse performance. Next, the BSC is used to evaluate warehouse performance from four perspectives: financial, customer, internal business processes, and learning and growth. The research results show that equipment reliability, labor efficiency, and inventory management are key areas that need to be improved to optimize warehouse performance. BSC analysis revealed the need to improve delivery timeliness, storage quality and efficiency of logistics processes. This research provides strategic insights for continuous improvement in PT warehouse operations. Sunan Rubber, supports strategic and operational decision making to increase efficiency and effectiveness.B